Interleukin-6 and Vitamin D Status during High-Intensity Resistance Training in Patients with Chronic Kidney Disease. (2nd April 2014) - Molsted, Stig; Eiken, Pia; Andersen, Jesper L.; Eidemak, Inge; Harrison, Adrian P.
Abstract : Background . The aim of this study was to investigate IL-6 and 25-hydroxyvitamin D (25-OH D) associations with muscle size and muscle function in dialysis patients. Methods . Patients were included in a 16-week control period followed by 16 weeks of high-intensity resistance training thrice weekly. IL-6 and 25-OH D were analysed after an over-night fast. Muscle fibre size was analysed in biopsies from m. vastus lateralis . Muscle power was tested using a Leg Extensor Power Rig. Results . Patients (n = 36 ) with IL-6 ≥ 6.49 pg/ml (median) were older and had decreased muscle power and a reduced protein intake (P < 0.05 ) compared with patients with IL-6 < 6.49 pg/ml. IL-6 was not associated with muscle fibre size. Vitamin D deficiency (25-OH D < 50 nmol/l) was present in 51% of the patients and not associated with muscle power. IL-6 remained unchanged during the training period, whilst muscle power increased by 20–23% (P < 0.001 ). Conclusion . Elevated IL-6 values were associated with decreased muscle power but not with decreased muscle fibre size. Half of the patients were suffering from vitamin D deficiency, which was not associated with muscle power. IL-6 was unchanged by high-intensity resistance training in dialysis patients in this study.